Nerve Biopsy. Issue 5 (1st October 2003) - Ginsberg, Lionel; King, Rosalind; Orrell, Richard
Abstract : INTRODUCTION It used to be said that a neurologist could diagnose the cause of a peripheral neuropathy in approximately 50% of cases on the basis of the history, examination and minimally invasive investigations – 'screening' blood and urine tests, chest X-ray, CSF examination and nerve conduction studies. About half the remainder would then be diagnosed by more specialized and invasive investigation, notably nerve biopsy, leaving approximately 25% of the original number cryptogenic. No doubt these proportions have changed with the increasing availability of specific DNA analysis for many of the genetic neuropathies, and the expanding range of serum autoantibodies associated with immunologically mediated neuropathies. Yet nerve biopsy remains an important diagnostic tool in patients with a progressive polyneuropathy of unknown aetiology, especially (but not exclusively) if asymmetrical. The emphasis on asymmetry (on clinical and/or electrical grounds) in this statement of the prime indication for nerve biopsy reflects the diagnosis most often